The Role of STEMI Communication Network in Malang with Major Adverse Cardiac Event (MACE) Incidence in STEMI Patients Hospitalized in Saiful Anwar General Hospital Malang - Adhika Prastya Wikananda; Lenny Kartika; Dadang Hendrawan; Heny Martini; Mohammad Saifur Rohman (Universitas Brawijaya, 2021)
Background: Patient with STEMI requires urgent reperfusion either with fibrinolytic or primary PCI. In Malang, a communication network of STEMI has been developed. It connects Saiful Anwar General Hospital with all of the PHC in Greater Malang to shorten system delay since 2015.Objective: To elucidate Malang’s communication network’s role in decreasing MACE (Major Adverse Cardiac Event) in STEMI patients.Methods : This is a retrospective cohort study. Study sample was taken from medical record. Non-network: 96 patients and 88 network patients. Statistical tests using SPSS and PLS, α value 0.05 and t-test is significant if more than 1.96.Results: Bivariate analysis shows network-group has a significantly lower MACE (p=0.001). Door-to-balloon time is also lower in network-group (p=0.026). Multivariate analysis without confounder shows that network-group has significantly shorter door-to-reperfusion time (p=0.032) and lower MACE (p=0.035) compared to non-network group. But multivariate analysis with confounder door-to-balloon and door-to-needle fails to explain lower MACE incidence. Network-group (p=0.005) and reperfusion with primary PCI (p=0.05) significantly decrease MACE incidence.Conclusion: Malang’s STEMI communication network and reperfusion with primary PCI reduce MACE in STEMI patients in Saiful Anwar General Hospital Malang.